The mechanism of miR-155-5p in regulating autism-like behaviour, pain sensitivity and inflammatory response in brain tissue via the Wnt/β-catenin pathway in valproic acid rat model of autism spectrum disorder - J. Zhao; X. Yin; L. Dong; X. Wang; X. Zhu; S. Xu; YC. Tang (The European Zoological Journal, 2025)
Autistic spectrum disorder (ASD), also known as autism, is a relatively serious developmental disorder. It is of great significance for patients to understand the pathogenesis of the condition and implement treatment. In this study, a valproic acid (VPA) rat model of ASD (VPA rats) is constructed; miR-155-5p was overexpressed by lentivirus, and rats were treated with ICG-001, an inhibitor of Wnt/β-catenin. The ASD behaviours were analysed in the VPA rats treated with and without ICG-001. The expression levels of brain tissue miR-155-5p, β-catenin, GSK-3β, cyclin-D1, c-myc and inflammatory factors are detected by ELISA and western blot. The results show that during a three-chamber sociability test, rats in the VPA group and miR-155-5p-mimics group had significantly decreased exploration time, longer dwell time in the middle compartment and reduced exploration time with the unfamiliar rat compared with the blank control group. The administration of ICG-001 significantly alleviated the above situation (p < 0.05). Similar results are observed in the open field test, self-grooming test and PWTL values, where ICG-001 administration significantly reduces the self-stroking time (p < 0.05). Compared with the blank control group, the relative expressions of β-catenin, GSK-3β, cyclin-D1, c-myc protein and inflammatory factors in rat brain tissues are increased in the VPA and miR-155-5p-mimics groups and decreased by ICG-001 treatment (p < 0.05). In summary, miR-155-5p affects the core clinical symptoms of VPA rats through the Wnt/β-catenin signalling pathway. Inhibition of miR-155-5p expression using ICG-001 can improve the core symptoms of social deficits, communication deficits, repetitive stereotypic behaviours and nociceptive thresholds in VPA rats, which provides an important basis for in-depth research on ASD clinical targeting.